HUBUNGAN KECEMASAN DENGAN MANAJEMEN DIRI PADA PASIEN DIABETES MELLITUS TIPE 2 DI MASA PANDEMI COVID-19 - Siska Rahmadiya; Dikha Ayu Kurnia (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Introduction : Diabetes mellitus type 2 is a metabolic condition brought on by either the body's ineffective use of insulin or diminished insulin synthesis by pancreatic ÃŸ-cells. People with Type 2 Diabetes Mellitus can self-manage their high blood sugar, called hyperglycemia.Â During the COVID-19 epidemic, Type 2 Diabetes Mellitus patients had trouble managing their condition on their own. The CoVID-19 pandemic has caused everyone's activities to be limited. People with diabetes mellitus saw a decline in their capacity to do self-care during the Covid-19 epidemic. This study was conducted to determine the relationship between anxiety and self-management of people with Type 2 DM during the COVID-19 pandemic.. Methods: This study's cross-sectional methodology approach and correlational research design involved 88 respondents. Result: The study's findings revealed that respondents who have low anxiety as many as 12 people (14.8%) have good self-management compared to respondents with moderate anxiety.Â The statistical test results obtained the p value of COVID-19 anxiety of 1.000 which means there is no relationship between anxiety and self-management.Conclusions : In order to maximize self-management during a pandemic or post-pandemic, researchers believe that nursing services will be able to evaluate the elements that affect the self-management of persons with Type 2 DM.